Using Critical Reflection to effect Dispositional Change toward Critical Thinking and Gain Insight into Student Learning - Steven D Koether (Adult Education Research Conference, 2018)
The purpose of this research roundtable is to discuss the use of Brookfield’s Critical Incident Questionnaire to effect dispositional change in students toward critical thinking, gain greater instructor insight, and improve instruction. My preliminary, and future, work in this area derives from experience with undergraduate students taking a general education science course.
Keywords: Critical Reflection; Disposition; Critical Thinking; Online; Science